Convergences and disparities of work orientations among recent graduates in Portugal - Chaves,Miguel (2016)
We aimed to identify patterns of work value orientations in a sample of graduates from two universities in Lisbon, and assess whether differences in extrinsic and intrinsic orientations can be explained by structural determinants of material living conditions. We found three common patterns: “aspirational maximalism”; importance of the job to gain financial autonomy from parents; and greater importance of intrinsic rewards. Results suggest the variation in the importance of extrinsic and intrinsic values bears little correlation with differences in material living conditions, and that subjects tend to adjust their work value orientations to their assessment of objective employment rewards.